Challenges and changes in arts education in Sweden – visual communication, visual culture and visual competence in the syllabus for visual arts. Issue 3 (2nd October 2022) - Karlsson Häikiö, Tarja
Abstract: The article problematizes conditions for visual arts education in Swedish compulsory school. This, by discussing the syllabus for visual arts (Sw. Bild) and through giving examples of teaching in the subject, based on interviews with visual arts teachers, carried out in connection with the production of two Assessment Guides on behalf of The National Agency for Education in 2012 and 2014. The subject visual arts are contextualized in relation to research in the subject field and the national evaluations in visual arts completed in 1992, 2003 and 2013. The research material is analyzed from a post-reflective perspective in relation to the 2011 syllabus (Lgr11) for visual arts, where visual communication and visual culture are central in defining the subject content. The research is further discussed in relation to the renewed syllabus for visual arts (Lgr22), operated in Swedish schools from school year 2022/2023, where a stronger emphasis emerges on visual competency. The syllabus and visual competency is discussed from a pre-reflective perspective and related to affiliated sub-competences defined by the European Network for Visual Literacy.